The Musical Idea and the Logic, Technique, and Art of its Presentation - Schoenberg, Arnold 1874-1951; Carpenter, Patricia; Neff, Severine (New York Columbia University Press, 1995)
The Gedanke manuscripts, from which The Musical Idea is compiled, are legendary writings of Arnold Schoenberg. Central to his concern was his concept of the "musical idea," which represents the wholeness of the musical work and embraces Schoenbergs notions of motive, gestalt, phrase, theme, rhythm, harmony, and form. Ultimately, the musical idea is the vision of the composer by which a musical work achieves unity in relation to the means by which the work is comprehended in its unity by the listener.
Keywords: Music philosophy and esthetics